# 1995 - WAEC Mathematics Past Questions and Answers - page 1

Find (101\(_2\))\(^2\), expressing the answer in base 2.

**correct option:**b

You can convert it to base 10 and square, then re-convert it after the operation.

OR

You can multiply it straight applying the rules of binary multiplication.

**correct option:**c

21 = N10.50

1 = 1050K/21 = 50K

6 = 6 x 50K = N3.00

7 = 7 x 50K = N3.50

8 = 8 x 50K = N4.00

the Largest share = N4.00

^{-4}

^{-3}

^{3}

^{4}

**correct option:**a

_{2}a = log

_{8}4, find a

^{1/3}

^{2/3}

^{2/3}

^{2/3}

**correct option:**d

_{2}a = Log

_{8}4

Log

_{2}a = Log

_{8}8

^{2/3}→ 2/3Log

_{8}8 → 2/3 x 1

Log

_{2}a = 2/3

Recall; If Log

_{a}x = y ∴ ay = x

Log

_{2}a = 2/3

2

^{2/3}= a

By selling some crates of soft drinks for N600.00, a dealer makes a profit of 50%. How much did the dealer pay for the drinks?

**correct option:**d

S.P = N600.00

(100 + 50)% = N600

150% = N600

1% = \(\frac{600}{150}\)

100% = \(\frac{600}{150} \times 100%\)

= N400

**correct option:**d

1st term = 11

A.P = a, a + d, a + 2d ...... a + (n - 1)d

If a = 11

a + d = 4

d = 4 - 11 = -7

nth term = a + (n-1)d

= 11 + (n-1)(-7)

= 11 - 7n + 7

= 18 - 7n

**correct option:**c

^{2}, ar

^{3}

ar

^{2}= 1 => 16r

^{2}/9 = 1 => 16r

^{2}

9 => r

^{2}= 9/16 => r = 3/4

ar

^{2}= y = ar

^{2}x r = 1 x 3/4 = 3/4

x xy = 4/3 x 3/4 = 1

If R = [2, 4, 6, 7] and S = [1, 2, 4, 8], then R∪S equal

**correct option:**a

R = {2, 4, 6, 7}; S = {1, 2, 4, 8}

R \(\cup\) S = {1, 2, 4, 6, 7, 8}

Find the value(s) of x for which the expression is undefined: \(\frac{6x - 1}{x^2 + 4x - 5}\)

**correct option:**b

\(\frac{6x - 1}{x^2 + 4x - 5}\)

The expression is undefined when \(x^2 + 4x - 5 = 0\)

\(x^2 + 5x - x - 5 = 0\)

\(x(x + 5) - 1(x + 5) = 0\)

\((x - 1)(x + 5) = 0\)

The expression is undefined when x = 1 or -5.

Which of the following could be the inequality illustrated in the sketch graph above?

**correct option:**b

Gradient of the line = \(\frac{3 - 0}{0 - 1}\)

= -3

y = -3x + b.

Using (1,0), we have

0 = -3(1) + b

0 = -3 + b

b = 3

y = -3x + 3

\(\therefore\) The graph illustrates y \(\leq\) -3x + 3.